Rapid Assessment of Proposed Reintroduction Sites for the Manipur’s Brow-antlered Deer or Sangai - Tuboi, Chongpi; Badola, Ruchi; Hussain, Syed Ainul (Indian Forester, 2018)
Manipur’s brow-antlered deer or sangai, is one of the most threatened species of deer found as a single, small and isolated population the Keibul Lamjao National Park (KLNP), Manipur. The major factors affecting its survival are its poor genetic status, deteriorating habitat conditions, lack of connectivity with the surrounding landscapes and mortality due to poaching and diseases. For its continuous existence in the wild, the best strategy is to create a second population at a suitable site that guarantees its long-term survival. Five sites with ecosystem components similar to those of KLNP, comprising wetlands (locally called Pat) and forest areas were surveyed. A qualitative ecological and disturbance scoring matrix was used to assess these sites. Pumlen Pat with adjoining Thongam Mondum Reserve Forest was identified as the best site for reintroduction of Sangai, which can be managed as a conservation reserve for the sustainable development of the area.